The nature and timing of landscape change at Cerro Benitez, Ultima Esperanza, southern Patagonia (52°S): New insights into the history of megafaunal extinctions and human occupation - McCulloch, Robert D.; Mansilla Andrade, Claudia Andrea; Martin, Fabiana Maria; Borrero, Luis; Staff, Richard A.; Tisdall, Eileen W. (My University, 2021)
A new Late glacial - Holocene palaeoenvironmental record from Cerro Benitez (51 degrees 33'S 72 degrees 35'W), Seno Ultima Esperanza, is presented. A pollen and spore record, from a closed basin mire, provides insight into the dramatic landscape changes spanning the past similar to 16,000 years. AMS radiocarbon dating, supplemented by the application of tephrochronology, provides robust age constraint. Our record of landscape change is set alongside a summary of the archaeofaunal records from the suite of caves and rock shelters that surround Cerro Benitez. Our record begins c. 16.3 ka, sometime after glacier retreat from the area, and describes a treeless landscape favoured by large grazing animals. At c. 14.9 ka, southern beech trees began to migrate into the area, but the landscape remained open with sufficient open ground for grazers. At c. 12.0 ka there was a dramatic expansion of woodland, but the decline of large mammals appears to have started some similar to 700 years earlier and is coincident with the arrival of hunter-gatherers in the area c. 12.7 ka. However, there is no archaeological evidence for human induced mass killing events, and it is likely that Cerro Benitez was a marginal resource area for early hunters that fell in and out of favour as the landscape changed during the Holocene; initially, less favourable during the early Holocene dry period (c. 11.0-8.0 ka) and more in favour during the mid-to late Holocene, although increasingly supplemented by more distant (similar to 5-10 km) materials, including marine resources from the Golfo Almirante Montt.
Keywords: pollen analysis; palaeoenvironments; late glacial; holocene; megafaunal extinctions; cave archaeology